A Maxillary Lateral Incisor with Type V Canal Morphology: A Case Report - Saide Nabavi,; Rezaei, Mahla; Sayeh Rahbaryfar, (Iranian Endodontic Journal, 2022)
A detailed root canal morphology description is of utmost importance for the success of endodontic treatment. Therefore, clinicians require a thorough knowledge of the root canal anatomy and its variations and anomalies in all the tooth types. This study reports a permanent upper lateral incisor exhibiting an uncommon root canal system morphology: a single-rooted tooth with one main root canal bifurcating into two distinct root canals in the apical third, with two apical foramina (Type V root canal morphology).